The Economic Importance of Improving Human Resource Management Expertise - Aliseevna, Chernova Tatiyana; Nazir, Naimjonov; Ikrom, Tairov (Journal of Innovation in Education and Social Research, 2024)
In this article, the opinions of our country's and foreign scientists are mentioned about the economic importance of improving human resource management expertise.